A system for improving the quality of real-time services on the internet - Bettermann, Stephan (Curtin University, 2013)
Real-time Internet services are becoming more popular every day, and Voice over Internet Protocol (VOIP) is arguably the most popular of these, despite the quality and reliability problems that are so characteristic of VOIP. This thesis proposes to apply a routing technique called Fully Redundant Dispersity Routing to VOIP and shows how this mitigates these problems to deliver a premium service that is more equal to traditional telephony than VOIP is currently.Fully Redundant Dispersity Routing uses the path diversity readily available in the Internet to route complete copies of the data to be communicated over multiple paths. This allows the effect of a failure on a path to be reduced, and possibly even masked completely, by the other paths. Significantly, rather than expecting changes of the Internet that will improve real-time service quality, this approach simply changes the manner in which real-time services use the Internet, leaving the Internet itself to stay the way it is.First, real VOIP traffic in a commercial call centre is measured (1) to establish a baseline of current quality characteristics against which the effects of Fully Redundant Dispersity Routing may be measured, and (2) as a source of realistic path characteristics. Simulations of various Fully Redundant Dispersity Routing systems that adopt the measured VOIP traffic characteristics then (1) show how this routing technique mitigates quality and reliability problems, and (2) quantify the quality deliverable with the VOIP traffic characteristics measured. For example, quantifying quality as a Mean Opinion Score (MOS) estimated from the measurements with the International Telecommunication Union’s E-model, slightly more than 1 in every 23 of the VOIP telephone calls measured in the call centre is likely to be perceived to be of a quality with which humans would be less than very satisfied. Simulations carried out for this thesis show that using just two paths adopting the same measurements, Fully Redundant Dispersity Routing may increase quality to reduce that proportion to slightly less than 1 in every 10 000 VOIP telephone calls.